KAJIAN PEMIKIRAN KEISLAMAN DAN KEBANGSAAN KH BISRI MUSTOFA REMBANGDALAM KITAB SYI’IR NGUDI SUSILA - Agus Salim Chamidi (Prodi MPI IAINU Kebumen, 2018)
This article is a research about Book Syi’ir Ngudi Susila written by KH Bisri Mustofa Rembang. The book (kitab) explaines about susila (moral, ethics, akhlakul karimah). The author of the book is a kyai founded pesantren Raudhatut Thalibin Leteh Rembang, and also a famaous politician. Research aims to know contents of the book and to find the author’s Islamic thoughts. Results refer those, (1)habitus and modal owned by the author (agent) much influence contents of the book, (2)this book is as a form of the santri’s cultural reproduction efforts, (3)through this book the author seems try to building profile of ‘anak Islam’ (santri, children of Islam) Nusantara whose have Islam ethics and nationality Indonesia. Keywords: Kitab Syi’ir Ngudi Susila, habitus, modal, cultural reproduction, santri Abstrak Tulisan ini merupakan riset tentang Kitab Syi’ir Ngudi Susila karya KH Bisri Mustofa Rembang.Kitab ini menjelaskan susila (budi pekerti, akhlakul karimah). Penulis kitab merupakan seorang kyai pendiri pesantren Raudhatut Thalibin Leteh Rembang dan juga seorang politisi handal. Riset ini bertujuan untuk mengetahui isi kitab dan menemukan pemikiran keIslaman penulis. Hasil riset menunjukkan bahwa, (1)habitus dan modal yang dimilik penulis (agen) banyak mempengaruhi isi kitab, (2)kitab ini merupakan wujud untuk upaya reproduksi kultural santri, (3)melalui kitab ini penulis nampaknya mencoba membangun profil ‘anak Islam’ (santri) Nusantara yang berakhlakul karimah sekaligus berwawasan kebangsaan Indonesia.